Participation of Dopamine D1 and D2 Receptors in the Rapid-Onset Behavioral Sensitization to Modafinil - Wuo-Silva, Raphael; Fukushiro-Lopes, Daniela F.; Fialho, Bruno P.; Hollais, André W.; Santos-Baldaia, Renan; Marinho, Eduardo A. V.; Mári-Kawamoto, Elisa; Yokoyama, Thaís S.; Lopes-Silva, Leonardo B.; Berro, Laís F.; Frussa-Filho, Roberto; Longo, Beatriz M. (Frontiers in Pharmacology, 2019)
Modafinil, a psychostimulant-like drug used to treat narcolepsy, has been shown to present effects that are similar to drugs of abuse, including the induction of the rapid-onset type of behavioral sensitization (i.e., a type of sensitization that develops within hours from the drug priming administration). The rapid-onset sensitization has emerged as a valuable tool to study the neuroplastic changes that occur quickly after drug administration and share neuroadaptations with drug abuse in humans. However, the mechanisms involved in the rapid-onset behavioral sensitization induced by modafinil are uncertain. Our aim was to investigate the possible involvement of dopamine D1 and D2 receptors on acute modafinil-induced hyperlocomotion and on the induction and expression of the rapid-onset behavioral sensitization induced by modafinil in male Swiss mice. Treatment with the D1 receptor antagonist SCH 23390 or the D2 receptor antagonist sulpiride attenuated the expression of acute modafinil-induced hyperlocomotion in a dose-dependent manner. Pretreatment with either antagonist before the priming injection of modafinil prevented the development of sensitization in response to a modafinil challenge 4 hours later. However, only SCH 23390 was able to decrease the expression of modafinil-induced rapid-onset behavioral sensitization. Taken together, the present findings provide evidence of the participation of D1 and D2 receptors on the development of rapid-onset behavioral sensitization to modafinil, and point to a prominent role of D1 receptors on the expression of this phenomenon.